Black Girls Swim: Race, Gender, and Embodied Aquatic Histories. Issue 2 (1st June 2021) - White, Samantha
Abstract: During the early part of the twentieth century, Black girls in the United States attended Young Women's Christian Associations (YWCAs) where they received instruction in sports and physical activity. Using archival research, in this article I examine the role of swimming in Black girls' sports and physical activity practices in Northern YWCAs. With a focus on the construction of Black girlhood, health, and embodiment, I trace how girls navigated spatial segregation, beauty ideals, and athleticism. I highlight the experiences of Black girl swimmers—subjects who have often been rendered invisible in the historical and contemporary sporting landscape.